An evaluation of the quality of online perinatal depression information - Madison P. Hardman; Kristin A. Reynolds; Sarah K. Petty; Teaghan A. M. Pryor; Shayna K. Pierce; Matthew T. Bernstein; Patricia Furer (BMC, 2022)
Abstract Background During the perinatal period (including pregnancy and up to 12 months after childbirth), expectant and new mothers are at an elevated risk of developing depression. Inadequate knowledge about perinatal depression and treatment options may contribute to the low help-seeking rates exhibited by perinatal people. The Internet can be an accessible source of information about perinatal depression; however, the quality of this information remains to be evaluated. The purpose of this study was to assess the quality of perinatal depression information websites. Methods After review, 37 websites were included in our sample. To assess overall website quality, we rated websites based on their reading level (Simple Measure of Gobbledegook; SMOG), information quality (DISCERN), usability (Patient Education Materials Assessment Tool; PEMAT), and visual design (Visual Aesthetics of Website Inventory; VisAWI). Results Websites often exceeded the National Institute of Health's recommended reading level of grades 6-8, with scores ranging from 6.8 to 13.5. Website information quality ratings ranged from 1.8 to 4.3 out of 5, with websites often containing insufficient information about treatment choices. Website usability ratings were negatively impacted by the lack of information summaries, visual aids, and tangible tools. Visual design ratings ranged from 3.2 to 6.6 out of 7, with a need for more creative design elements to enhance user engagement. Conclusions This study outlines the characteristics of high-quality perinatal depression information websites. Our findings illustrate that perinatal depression websites are not meeting the needs of users in terms of reading level, information quality, usability, and visual design. Our results may be helpful in guiding healthcare providers to reliable, evidence-based online resources for their perinatal patients.